An Assessment of the Service Quality Delivery in Tertiary Education – A Case Study of Pentecost University College, Ghana - Annor, Kwasi Asante (2013)
A Thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirements for the degree of Commonwealth Executive Masters of Business Administration, September-2012